Development of perovskite based light emitting diodes with improved stability 4.0 - Yap, Alvin Yong Jun (Nanyang Technological University, 2021)
The CsPbX3 (X = Cl, Br, I) nanocrystals (NCs) are emitting materials for illumination & display because of their remarkable photophysical properties. However, a big problem with the perovskites is that it faces a issue of overcoming its poor stability. With environmental conditions causing this degradation which in turns affected this perovskites materials. Basedon external research it is also found that by having the ligands replaced which involve the use of the Microwave irradiation method, it will produce better stability which is measured by higher yield. Perovskite quantum dots (QD) is semiconducting NC which is being synthesised using perovskites which is a luminescence material which can be displayed in the LED. They have outstanding performance. Perovskites QD have higher quality of photoluminescence quantumyieldand colour. Their traits make them suitable to be use in display technology as they have excellent speed in terms of emitting light sources. The key concern is still the degradation of perovskites which can accelerate due to bad climate condition. Hence experiments are carried out to improve the stability of the perovskite. Perovskite nanocrystals have unique qualities which makes them better then Perovskite quantum dots such as their unusually structured band which makes this materials more defect resistance and make them able to produce light brightly without surface passivation.